A photonumeric scale for the assessment of atrophic facial photodamage. (1st May 2018) - Ayer, J.; Ahmed, A.; Duncan‐Parry, E.; Beck, P.; Griffiths, T.W.; Watson, R.E.B.; Griffiths, C.E.M.
Summary: Background: Photonumeric scales have consistently shown superiority over descriptive equivalents. They have the advantage of providing a consistent visual frame of reference by minimizing variability in perception and subjectivity. A photonumeric scale to assess hypertrophic facial photodamage already exists. However, there is currently no objective measure for atrophic facial photodamage. To address this, we have devised a nine‐point photonumeric standardized scale. Objectives: To design, test and validate a photonumeric scale for the assessment of atrophic facial photodamage against a descriptive scale for the same indication. Methods: A pool of 393 facial photographs ( en face and 45° oblique) from 131 individuals with atrophic facial photodamage was created. Five photographic standards were selected and assigned grades zero through to eight, where zero is no photodamage and eight is severe atrophic photodamage, thus making a nine‐point scale. Twenty photographs spanning the entire range of values were selected to test the scale. Testing was performed alongside a descriptive equivalent. A panel of 10 dermatologists, 10 nondermatology clinicians and 14 dermatology scientists marked the two scales; marking was repeated 1 week later. Results: There was a significantly greater agreement between the graders using the photonumeric scale than the descriptive scale (kappa values 0·71 and 0·37 with standardized errors of 0·57 and 0·17, respectively) with no significant difference in repeatability between the two methods ( P < 0·05). Conclusions: The study describes a new photonumeric scale for atrophic photodamage. This would be a useful adjunct in both the clinical and research settings.